Employee Attendance System using Face Recognition Using LBP Method - Sahoo, Ashok Kumar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
In the field of computer vision, the study of face recognition technologies is becoming an increasingly important area of research. This technology can be useful in a variety of settings, including those involving security and surveillance, biometrics, and the interaction between humans and computers. (HCI). Deep learning models, such as convolutional neural networks, have made it feasible to create face recognition systems that are both accurate and scalable. These systems are already in widespread use. These advancements are a direct consequence of the models that were utilised in the making of them. Despite this, there are still a lot of obstacles that need to be overcome, such as developing systems that are more open-minded and objective, as well as figuring out how to account for changes in posture, expression, and lighting. This article presents a comprehensive examination of the innovative techniques that are now being employed for face recognition. Deep learning is an example of a more contemporary methodology, whereas local binary patterns are an example of an earlier approach to machine learning. In addition, we analyse the numerous challenges and confinements posed by these methods and present some potential answers to the issues that have been raised. In addition to this, we investigate the moral and legal implications of employing facial recognition technology, as well as the preexisting datasets that are typically put to use for this kind of research. The one of the section of this investigation will centre on the characteristics and characteristics that are crucial to the effective operation of a face recognition system. As research and development activities are carried on into the foreseeable future, there will be a great deal of fascinating progress made in this area. These advancements have the potential to significantly improve both safety and comfort in a variety of settings.